Innovative Learning Landscapes: The Impact of Canva and Problem-Based Learning on Student Engagement - Emma Rumahlewang; Izak Jakobis Makulua; Johanna Matitaputty (Unram Journal of Community Service, 2026)
Community service activities based on system-supported learning have become an alternative approach to maintaining effective teaching and learning processes under various conditions. However, several challenges remain, including low student motivation in system-based learning environments. Therefore, an engaging learning approach is needed to create a more interactive learning experience and improve motivation. Canva is a digital application that can be utilized by Sunday school teachers to develop creative and engaging learning media. This community service activity aimed to improve the ability of Sunday school teachers to utilize the Canva application through a Problem-Based Learning (PBL) approach. The implementation method involved training, mentoring, questionnaires, and interviews to evaluate the outcomes of the activity. This program was conducted at Nehemiah Congregation, Ambon City, Indonesia, involving Sunday school teachers and students aged 11–14 years, with a total of 40 participants. The evaluation results showed an improvement in participants’ abilities before and after the training activities. Prior to the training, 8 participants (25%) were unable to use the Canva application, while 28 participants (75%) demonstrated only a moderate level of proficiency. After the training, 34 participants (96%) were able to use the Canva application effectively. In terms of usefulness, 35 participants (90%) stated that learning through the Canva application was very beneficial, while 1 participant (10%) considered it beneficial. These findings indicate that community service activities involving Canva training using the PBL approach had a positive impact on improving participants’ ability to create creative and engaging learning media.